Analysis of West Sumatra's Tourism Attraction on The Development of The Minangkabau International Airport Area - Anggraini, Kurnia; Wibowo, Adi (Politeknik Negeri Batam, 2024)
The West Sumatra region is very rich in tourism potential, in the form of natural beauty and culture which makes many tourists come to the West Sumatra area. The aim of this research is to analyze the tourist attractions in West Sumatra regarding the development of the Minangkabau International Airport area. The method used in the research uses a qualitative descriptive approach to analyze the tourist attractions in West Sumatra regarding the development of the airport area. The data used to analyze tourist attractions uses secondary data from various related agencies. The development of the airport area uses a remote sensing approach, namely, the digitization method on Google Earth images carried out on Google Earth Pro Software in 2013 and 2023. The results of the research conclude that aircraft movements and passenger movements have increased. From the results of digitization via Google Earth in 2013 and 2023, over the last 10 years, the airport area has experienced development, especially the aircraft parking area, passenger terminal, car parking area, in 2023 there will be additional buildings, namely, the airport station.